‘WAR IS NOT ALWAYS VIOLENT AND VIOLENCE IS NOT ALWAYS WAR.’ — AN ANECDOTE ON HOW LANGUAGE AND ULTIMATELY THE LAW IS USED TO PERPETUATE EPISTEMIC VIOLENCE IN SOUTH AFRICA (The Pretoria Student Law Review, 2021)
The focus of this paper will be how linguicide is used as a mechanism to perpetuate epistemic violence in South Africa and how epistemic diversity is needed in order for those who find themselves ‘below the law’ to ascertain access to justice. Firstly, I will define the concepts ‘linguicide’ and ‘epistemic violence.’ Secondly, I will offer a critique on how the English language is not neutral but rather a socioeconomic tool that shapes power relations within society. Thirdly, I will introduce the critical theories of Black Consciousness and Marxism to show how the law is complicit in perpetuating racial and class inequalities in South Africa. I will then conclude with how access to justice can become a reality through the paradigm of decolonisation (‘of the mind’) as understood by various African authors and provide recommendations of an imagined alternative.
Keywords: linguicide; epistemic violence; South Africa; epistemic diversity; access to justice; critical theories; Black Consciousness; Marxism; decolonisation